Three new neotropical species of Ablabesmyia Johannsen, 1905 (Diptera: Chironomidae) - Dantas, Galileu P.s.; Hamada, Neusa (Zootaxa, 2019)
Three new species of Ablabesmyia are described from Brazil: A. akemiae sp. n. based on the male, female, pupa and larva; A. adamantis sp. n. based on the male, pupa and larva; and A. monticola sp. n. based on the adult male. Ablabesmyia akemiae sp. n. immatures were collected in a small river associated to aquatic vegetation, A. adamantis sp. n. larva was collected in a first order stream associated with accumulated fallen leaves, and adults of A. monticola sp. n. were collected with light-traps, in a mountainous region at about 1000 m altitude.